"Study on Performance of Wonogiri Reservoir for Flood Control in Relation to Uncertainty of Inflow Flood Hydrograph." - Rachmad Jayadi, author 1 (2009)
MUWAREC International Conference on Sustainable Development for Water and Wastewater Treatment Muslim Water Researchers Cooperation